IMPACT OF FOREST FIRES ON PORTUGUESE FOREST ECOSYSTEM AND ITS NATIONAL EMISSIONS BUDGET - Pavel, Muha Abdullah Al; Marques, Mario; Mukta, Kamrun N (Indonesian Journal of Forestry Research, 2024)
The study highlights the significance of the forestry industry in Portugal, and delves into the economic, social, and environmental ramifications of forest fires on this vital sector. With a specialization in forest services, the country's healthy and sustained growth is heavily reliant on this sector. The study is a literature review analysis of carbon sink-source relationships and related uncertainty in the Portuguese forest ecosystem. We found wide literature research that Portugal lost 4% of its total tree cover due to forest fires in 2016-2017. The study concludes that the drought and forest fires suffered by the country throughout the years have had a considerable impact on the national emissions budget. Forest fires have wielded a significant impact on the nation's overall carbon emissions, representing 10% during the years with the highest incidence and averaging 2.7% over 25 years. Prior to 2014, the country was making significant progress towards achieving its National Plan on Climate Change (PNAC) 2020 reduction target, with emissions projected to fall between 18-23% below 2005 levels. These factors are putting country in a non-compliance position with the PNAC 2020 commitment target (which is the same target as for the Kyoto Protocol 2nd Commitment Period).